Responsability of sponsors after clinical trials are finished - Benites Estupiñán, Elizabeth (Acta Bioethica, 2006)
This paper describes some ethical problems derived from multi center studies in developing countries, specifically those referred to the role of sponsors after the clinical trial is concluded. After reviewing some international norms, it proposes several ethical obligations fro sponsors of these trials. Finally, the evidence shows pessimism with respect to fulfilling them.